Lab Coat and Turban, a Tribute to Robert G. Jahn - Nelson, Roger D. (Journal of Scientific Exploration, 2018)
We have lost a friend, a valued colleague, and an inspirational mentor in the passing of Professor Robert G. Jahn, the founder and director of Princeton Engineering Anomalies Research (PEAR). He was one of the prominent academics who came together to create the Society for Scientific Exploration in the early 1980’s, and he served as SSE’s Vice President for more than three decades. His was a voice on the SSE Council that we listened to with special attention, because he was himself such a talented listener, able to summarize what was important for decisions that would affect the course of SSE’s growth and its value to the research community. Bob’s career touched and influenced the farthest reaches of science, from the physics of electric propulsion for spacecraft to the extended capacities of human consciousness. A partial listing of his accomplishments and honors give a hint of his breadth of interests. Bob was Dean of the School of Engineering and Applied Science at Princeton University from 1971 to 1986. He was a Fellow of the American Physical Society and of the American Institute of Aeronautics and Astronautics, and an influential member of numerous other technical organizations. He was Chairman of the Board of the International Consciousness Research Laboratories consortium. He was a member of the Board of Directors of Hercules, Inc. and Chairman of its Technology Committee, and Chairman of the Board of Trustees of Associated Universities, Inc. This is a small sample of the long list of Bob’s achievements, but it is safe to say that with all his extraordinary contributions in science and technology, his deepest feelings of accomplishment were for the study of consciousness at the frontiers of our understanding.